Analisis Peran Media dalam Mempengaruhi Keberlanjutan Kerjasama Joint Production Kapal Selam Changbogo dan Pesawat Tempur KF-X/ IF-X antara Indonesia dan Korea Selatan - Endro Tri Susdarwono (Jurnal Digital Media dan Relationship, 2020)
The purpose of this study discusses the analysis of the role of the media in influencing the continuing joint production of Changbogo submarines and KF-X / IF-X fighter aircraft between Indonesia and South Korea. This research is a qualitative research, the type of research uses a comprehensive analytical study and analytical normative approach. In the latest media developments, there are at least two main interests behind the media, namely economic interests and power interests, which shape the contents of the media, the information presented, and the meaning it offers. The news, which is manifested in certain themes which then either intentional or not, cones into several news themes that tend to favor the sustainability of joint production of joint production of Changbogo submarines and KF-X / IF-X warplanes. The themes raised by the main media in the media coverage of the territorial sovereignty of the Indonesian sea, the triumph of the Indonesian Navy in particular about the Submarine Corps and the Air Force-Soekarno-era, the rampant theft of fish and sea sand in Indonesian territory, violations of the territorial sovereignty of the Indonesian sea and air are caused by the weakness of Indonesia's defense equipment in protecting its territory, as well as media coverage of the modernization of Indonesia's defense equipment mainly about cooperation in making Changbogo submarines and KF-X / IF-X warplanes between the Governments of Indonesia and South Korea.